Birth order, suckling behaviour and growth in piglets: a case study of the extreme delay in birth of two surviving piglets - Lončarič, Ana; Prevolnik Povše, Maja; Skok, Janko; Škorjanc, Dejan (Agricultura Scientia, 2021)
In pigs, higher birth order is associated with higher mortality rate, with abnormal delays in birth as a rule result in a prenatal death. Here we present a case study of an extreme delay in birth of two surviving piglets (delayed piglets) which were born 15 h after the beginning of parturition and 12 h after the last piglet of the main episode of the parturition (n=12) was born. The rest of the observed litter was divided into early born (n=6, born within 80 min) and late born piglets (n=6, born within the next 80 min from the beginning of parturition). Suckling behaviour, survival and growth performance of piglets were studied in relation to birth order whereby special attention was given to the delayed piglets. In general, suckling stability tended to decrease with birth order with the delayed piglets having completely unstable suckling. In the first suckling, piglets predominantly chose posterior teats, but later, when suckling order was established, early born piglets preferentially sucked on the front half and the late born piglets on the back half of the udder. The delayed piglets suckled on the middle teats immediately after birth, but later they chose preferential teats on different parts of udder (2nd and 6th teat pair). Growth performance of delayed piglets was lower, although not significantly (probably due to small sample size), compared to the late and especially to the early born group. Despite an extraordinarily long delay in birth, there was no clear association with the suckling order and its stability, the birth/body weight and daily gain. However, survival of piglets after that long delay in birth itself represents an extraordinary phenomenon that we cannot explain.